STUDY OF SOME MECHANICAL PROPERTIES OF THIN HARD COATING CHROMIUM CARBIDES (Sciences & Technology. A, exactes sciences, 2004)
In the present work, some mechanical properties of chromium carbides coating on steel substrates werestudied. The samples were prepared by d.c. magnetron sputtering of a pure Chromium (Cr) layer on steelsubstrates containing 1%wt of Carbon. The system (substrate/coating) was then annealed in vacuum at atemperature at which the carbon of the substrate may diffuse into the Cr metallic film. This fact leads to theformation of chromium carbides, which are identified by X-ray diffraction as Cr7C3, Cr23C6 and (Cr,Fe)7C3.The study by nanoindentation shows that the microhardness decreases with increasing of annealingtemperature until 800°C, then increases rapidly to reach a maximum (≈2800 Kg.mm-2) at 1000°C. Theinternal stresses, measured by X-ray diffraction, are compressive at 900°C and tensile at 1000°C in thechromium coating. Nevertheless, they are tensile in the substrates regardless the temperature. The signchange of the stresses in the coating is probably due to the phase transformation (Cr7C3→(Cr,Fe)7C3)).